Retrieval of Chronically Implanted Dual-chamber Leadless Pacemakers in an Ovine Model - Banker, Rajesh S; Rippy, Marian K; Cooper, Nicole; Neužil, Petr; Exner, Derek V; Nair, Devi G; Booth, Daniel F; Ligon, David; Badie, Nima; Krans, Mark; Ando, Kenji; Knops, Reinoud E; et al. (Circulation. Arrhythmia and electrophysiology, 2023)
BACKGROUND: The clinical utilization of leadless pacemakers (LPs) as an alternative to traditional transvenous pacemakers is likely to increase with the advent of dual-chamber LP systems. Since device retrieval to allow LP upgrade or replacement will become an important capability, the first such dual-chamber, helix-fixation LP system (Aveir DR; Abbott, Abbott Park, IL) was specifically designed to allow catheter-based retrieval. In this study, the preclinical performance and safety of retrieving chronically implanted dual-chamber LPs was evaluated. METHODS: Atrial and ventricular LPs were implanted in the right atrial appendage and right ventricular apex of 9 healthy ovine subjects. After ≈2 years, the LPs were retrieved using a dedicated transvenous retrieval catheter (Aveir Retrieval Catheter; Abbott) by snaring, docking, and unscrewing from the myocardium. Comprehensive necropsy/histopathology studies were conducted to evaluate device- and procedure-related outcomes. RESULTS: At a median of 1.9 years postimplant (range, 1.8-2.6), all 18 of 18 (100%) LPs were retrieved from 9 ovine subjects without complications. The median retrieval procedure duration for both LPs, from first-catheter-in to last-catheter-out, was 13.3 minutes (range, 2.5-36.4). Postretrieval, all right atrial, and right ventricular implant sites demonstrated minimal tissue disruption, with intact fibrous tissue limited to the distal device body. No significant device-related trauma, perforation, pericardial effusion, right heart or tricuspid valve injury, or chronic pulmonary thromboembolism were observed at necropsy. CONCLUSIONS: This preclinical study demonstrated the safe and effective retrieval of chronically implanted, helix-fixation, dual-chamber LP systems, paving the way for clinical studies of LP retrieval.
Keywords: kardiostimulátor; Sheep; feasibility study; Humans; intracardiac catheters; lipopolysacharidy; Sheep, Domestic; Equipment Design; Lipopolysaccharides; lidé; Atrial Fibrillation; right ventricle; zvířata; right atrium; ovce domácí; preclinical; design vybavení; Heart Ventricles; cardiac pacemaker, artificial; Animals; Pacemaker, Artificial; srdeční komory; fibrilace síní; ovce